A Description of a Graves’ Disease Patient Who Had Negative Serology after COVID-19 - Manov, A.; Badi, Y.; Wang, A.; Haddadin, R. (Disease and Health Research: New Insights Vol. 8, 2024)
A case of a 62-year-old African-American female who was admitted to our Emergency Department (ED) with septic shock due to pneumonia and sigmoid diverticulitis, has been presented. After improvement of the admitting conditions, it was found out that the patient had 1-month ago COVID-19 pneumonia. Clinical signs of thyrotoxicosis developed after the resolution of the COVID-19 pneumonia and before her current admission to the ED for septic shock. The patient had no thyroid diseases or complaints related to the thyroid gland before her infection with COVID-19. The clinical picture was highly suggestive of GD. A trill was palpated and a bruit was heard on her thyroid gland, which are specific findings of the hypervascular gland, as in GD. The patient complained of increased sweating, palpitation, lower extremities weakness, and lack of sleep before the septic shock and after the COVID-19 infection. Our physical findings were confirmed by the laboratory findings of thyrotoxicosis with increased total and free thyroxin levels and free triiodothyronine levels (TT4, FT4, and FT3) and very low thyroid stimulating hormone (TSH). The Doppler flow ultrasound of the thyroid gland confirmed the bilateral hypervascular gland suggestive of hyperthyroidism without nodules. The patient serological studies were negative for Thyroid-stimulating immunoglobulin (TSI) and thyroid receptor antibodies (TRAB) which have been described in 1-5% of patients with GD. This is, as far as known, the first described patient post-COVID-19 induced GD with negative serology.